Teacher Strategies for Developing Creative Character in Muhammadiyah Elementary Students: Strategi Guru dalam Mengembangkan Karakter Kreatif pada Siswa Sekolah Dasar Muhammadiyah - Kharisma, Risnanda Arilla; Indrakurniawan, Machful (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character education has become a vital foundation in Indonesian schools, aiming to cultivate students who are not only knowledgeable but also creative and responsible citizens. Specific Background: In Muhammadiyah elementary schools, particularly at Muhammadiyah 8 Tulangan, challenges persist as creativity is often difficult to assess, and many students show low confidence in their potential. Knowledge Gap: Limited studies explore teacher strategies in fostering creative character within Muhammadiyah educational settings. Aims: This study seeks to provide an in-depth description of teacher strategies in developing creative character among grade IV students. Results: Using qualitative descriptive methods with interviews, observations, and documentation, the findings show that teachers implemented interactive approaches such as discussions, debates, and discovery learning to stimulate students’ creative thinking. Students demonstrated improved confidence, the ability to generate original ideas, and active participation in learning activities. Novelty: The research highlights the integration of character education with creative learning strategies in a Muhammadiyah school context, showing how these methods strengthen both academic and personal growth. Implications: The study underscores the importance of structured character-based teaching strategies to nurture creativity, providing practical insights for teachers and educational policymakers in shaping creative and confident learners. Highlights: Creative character linked with students’ confidence and self-concept. Teacher strategies foster interactive and student-centered learning. Practical insights for Muhammadiyah schools in character development. Keywords: Teacher Strategies, Creative Character, Muhammadiyah School, Qualitative Research, Elementary Education